Treatment seeking by individuals with obsessive-compulsive disorder from the British Psychiatric Morbidity Survey of 2000 - Torres, Albina R. [UNESP]; Prince, Martin J.; Bebbington, Paul E.; Bhugra, Dinesh K.; Brugha, Traolach S.; Farrell, Michael; Jenkins, Rachel; Lewis, Glyn; Meltzer, Howard; Singleton, Nicola (American Psychiatric Association Publishing, 2007)
Objective: For several reasons, many individuals with obsessive-compulsive disorder (OCD) do not seek treatment. However, data on treatment seeking from community samples are scant. This study analyzed service use by adults with OCD living in private households in Great Britain. Methods: Data from the British Survey of Psychiatric Morbidity of 2000, in which 8,580 individuals were surveyed, were analyzed. Service use was compared for those with OCD, with other neuroses, with different subtypes of OCD (only obsessions, only compulsions, or both), and with OCD and comorbid neuroses. Results: Persons with OCD (N=114) were more likely than persons with other neuroses (N=1,395) to be receiving treatment (40% compared with 23%, p<.001). However, those with OCD alone (N=38) were much less likely than those with OCD and a comorbid disorder to be in treatment (14% compared with 56%, p<.001). In the previous year, 9.4% of persons with OCD had seen a psychiatrist and 4.6% had seen a psychologist. Five percent were receiving cognitive-behavioral therapy, 2% were taking selective serotonin reuptake inhibitors, and 10% were taking tricyclics. Conclusions: Most persons with OCD were not in contact with a mental health professional, and apparently very few were receiving appropriate treatments. Very few persons with noncomorbid OCD were receiving treatment. Individuals with OCD who are in treatment may not be disclosing their obsessions and compulsions and may be discussing other emotional symptoms, leading to inappropriate treatment strategies. Public awareness of OCD symptoms should be raised, and primary care professionals should inquire about them with all patients who have depressive or anxiety disorders.